2017
DOI: 10.1007/s10826-017-0711-y
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Paternal Influences on Children’s Coping with Cancer-Related Stress

Abstract: Childhood cancer is a significant source of stress for children and families, and children’s coping with cancer-related stress is a key predictor of emotional adjustment. To extend understanding of the determinants of children’s coping with cancer-related stress, this study examined whether mothers’ and fathers’ functioning after their child’s diagnosis—including coping and depressive symptoms—is predictive of children’s coping over time. Participants included 166 children (Mage = 13.47, SD = 2.47, 51.2% femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 53 publications
(85 reference statements)
2
12
1
3
Order By: Relevance
“…Uncertainties related to the experience of dealing with a chronic disease in childhood and adolescence have been predictors of suffering, anxiety and depression for parents (Monti et at., 2017;Pai et al, 2007). Anxiety and depression are understood as emotional problems, with different symptoms, with depression being understood as a clinical disorder characterized by depressed mood; anxiety, on the other hand, is characterized by the presence of excessive and uncontrollable concerns about different aspects of life (Cunha, 2001).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Uncertainties related to the experience of dealing with a chronic disease in childhood and adolescence have been predictors of suffering, anxiety and depression for parents (Monti et at., 2017;Pai et al, 2007). Anxiety and depression are understood as emotional problems, with different symptoms, with depression being understood as a clinical disorder characterized by depressed mood; anxiety, on the other hand, is characterized by the presence of excessive and uncontrollable concerns about different aspects of life (Cunha, 2001).…”
mentioning
confidence: 99%
“…Findings about predictors of anxiety and depression in chronic disease are relevant, since depressive symptoms in parents can limit their resources for teaching coping strategies for the child to effectively deal with chronic disease (Monti et al, 2017). In the context of chronic diseases, some findings have shown that mothers with depression are less able to suggest adaptive coping strategies to their children (Monti et al, 2017); and that parents in this emotional context may find it more difficult to assist their children in managing disease-related stress (Alves, Guirardello, & Kurashima, 2013), may be less responsive to their children's needs and more disconnected with them (Lovejoy, Graczyk, O'Hare, & Neuman, 2000). It is understood, therefore, that emotional variables, such as anxiety and depression of parents or legal guardians, can negatively interfere in the development of children and adolescents affected with a chronic disease, such as sickle cell anemia (Kazak et al, 2003).…”
mentioning
confidence: 99%
“…Murphy et al (2017) found that maternal positive emotionality predicts positive emotionality and lower levels of PTSSs in the child. The effect of parental well-being on child coping with cancer has been empirically supported by Monti et al (2017) as well. This study suggests positive child adjustment to cancer may be promoted through interventions targeting parent's own psychosocial functioning, especially their own coping and depressive symptoms.…”
Section: Socialization Of Coping With Childhood Cancermentioning
confidence: 93%
“…This study suggests positive child adjustment to cancer may be promoted through interventions targeting parent's own psychosocial functioning, especially their own coping and depressive symptoms. Moreover, Monti et al (2017) found that the parent-child association in coping may be time-specific. Mother-child association in coping emerges earlier with more immediate effect, whereas father-child association emerges later with the effect unfolding over time.…”
Section: Socialization Of Coping With Childhood Cancermentioning
confidence: 99%
See 1 more Smart Citation